Negative electrode, preparation method thereof and all-solid-state battery

By using metal powder to replace carbon-based conductive materials in the negative electrode of all-solid lithium-ion batteries, the problems of solid electrolyte decomposition and poor conductivity caused by carbon materials are solved, and higher cycling performance and rate performance are achieved.

CN119447182AInactive Publication Date: 2025-02-14SHANGHAI SAIC QINGTAO ENERGY TECH CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411736294.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-02-14
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

In existing all-solid-state lithium-ion batteries, carbon material conductive agents lead to decomposition of solid electrolytes and poor ionic conductivity, resulting in deterioration of cycling and rate performance.

Method used

Use metal powders (such as indium powder, tin powder, magnesium powder, copper powder, aluminum powder, iron powder) to replace carbon-based conductive materials to form a negative electrode active material layer with high electronic conductivity, and combine silicon powder to enhance the ionic conductance of the negative electrode. rate and mechanical strength.

Benefits of technology

It effectively reduces the decomposition of solid electrolytes, improves the electron and ionic conductivity of the negative electrode, improves the cycle performance and rate performance of the battery, and reduces the risk of cracking of the negative electrode.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention relates to a negative electrode, a preparation method thereof and an all-solid-state battery in the technical field of lithium battery production, the negative electrode comprises a negative electrode active material layer, the negative electrode active material layer comprises silicon powder and metal powder, and the electronic conductivity of the metal powder is 104-107 S / cm. According to the lithium ion battery, the metal powder is adopted in the negative active material layer to replace a carbon material serving as a conductive agent, on one hand, decomposition of solid electrolyte caused by the carbon material can be effectively reduced, and on the other hand, due to the good conductivity of the metal powder, the electronic conductivity of a negative electrode system can be effectively improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium battery production, and in particular to a negative electrode and a preparation method thereof, and an all-solid-state battery. Background Art

[0002] In recent years, the market demand for high energy density and high safety lithium-ion batteries has continued to accelerate. Compared with traditional liquid lithium-ion batteries, all-solid-state batteries have the technical advantages of high energy density and good safety. They have become a revolutionary energy storage technology and are the focus of research and development of domestic and foreign companies and research institutes. The performance of all-solid-state batteries is significantly affected by the performance of the negative electrode. Silicon-based negative electrodes have become one of the most promising next-generation all-solid-state battery negative electrode materials because of their ultra-high theoretical specific capacity (4200mAh / g) and low lithium insertion potential.

[0003] Silicon-based negative electrodes usually include silicon materials, binders and conductive agents. Existing conductive agents are usually carbon materials, which can cause the solid electrolyte in solid-state batteries to decompose and produce byproducts with poor ion conductivity at the interface between the negative electrode and the solid electrolyte membrane, thereby causing the cycle performance and rate performance of all-solid-state batteries to deteriorate.

[0004] The market is in urgent need of a technical solution to solve the above problems. Summary of the invention

[0005] In order to solve the above problems, the present invention discloses a negative electrode and a preparation method, and an all-solid-state battery. The technical solution of the present invention is implemented as follows:

[0006] The first aspect of the present invention provides a negative electrode for an all-solid-state battery, wherein the negative electrode comprises a negative electrode active material layer, wherein the negative electrode active material layer comprises silicon powder and metal powder, wherein the electronic conductivity of the metal powder is 10 4 S / cm~10 7 S / cm.

[0007] Preferably, the metal powder includes at least one of indium powder, tin powder, magnesium powder, copper powder, aluminum powder and iron powder.

[0008] Preferably, based on 100% of the mass of the negative electrode active material layer, the mass of the metal powder accounts for 10% to 30%.

[0009] Preferably, the particle size of the silicon powder is 1 μm to 6 μm, and the particle size of the metal powder is 0.05 μm to 3 μm.

[0010] Preferably, the negative electrode does not contain carbon-based conductive material.

[0011] Preferably, the porosity of the negative electrode active material layer is 5% to 12%.

[0012] Preferably, the negative electrode active material layer further includes a binder.

[0013] Preferably, based on 100% of the mass of the negative electrode active material layer, the mass proportion of the binder is 0.1% to 2%.

[0014] A second aspect of the present invention provides a method for preparing a negative electrode, the method comprising the following steps:

[0015] S1, mixing silicon powder, metal powder and a binder in a solvent to form a negative electrode slurry;

[0016] S2, coating the negative electrode slurry onto a negative electrode current collector, and drying to form a negative electrode.

[0017] The third aspect of the present invention proposes an all-solid-state battery, comprising a positive electrode, a solid electrolyte membrane and a negative electrode, wherein the negative electrode is the negative electrode as described in the first aspect or the negative electrode prepared by the method as described in the second aspect, and the negative electrode does not contain a solid electrolyte.

[0018] The advantages of the present invention are as follows:

[0019] In the present invention, metal powder is used in the negative electrode active material layer to replace the carbon-based conductive material. On the one hand, the decomposition of the solid electrolyte caused by the carbon material can be effectively reduced. On the other hand, due to the good conductivity of the metal powder, the electronic conductivity of the negative electrode system can be effectively improved. DETAILED DESCRIPTION

[0020] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0021] Unless otherwise defined, all technical and scientific terms used in the present invention have the same meanings as those commonly understood by technicians in the technical field to which the present invention belongs; the terms used in the specific implementation methods are only for the purpose of describing specific embodiments and are not intended to limit the present invention; the terms "including" and "having" in the specification and claims of the present invention and the above description and any variations thereof are intended to cover non-exclusive inclusions.

[0022] In the description of the specific implementation methods of the present invention, the technical terms "first", "second", etc. are only used to distinguish different objects, and cannot be understood as indicating or implying relative importance or implicitly indicating the number, specific order or primary and secondary relationship of the indicated technical features. In the description of the embodiments of the present invention, the meaning of "multiple" is more than two, unless otherwise clearly and specifically defined.

[0023] Reference to "embodiments" in the present invention means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present invention. The appearance of the phrase in various places in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described in the present invention may be combined with other embodiments.

[0024] In the description of the embodiments of the present invention, the term "and / or" is only a description of the association relationship of associated objects, indicating that three relationships may exist. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. In addition, the character " / " in the present invention generally indicates that the associated objects before and after are in an "or" relationship.

[0025] Throughout the present invention, numerical values ​​represent approximate measures or limits of ranges to cover minor deviations from given values ​​as well as embodiments with about the values ​​mentioned and embodiments with the exact values ​​mentioned. Except for the working examples provided at the end of the detailed description, all numerical values ​​of parameters (e.g., amounts or conditions) in this specification (including the appended claims) should be understood to be modified by the term "about" in all cases, regardless of whether "about" actually appears before the numerical value. "About" indicates that the stated numerical value allows some minor imprecision (close to the exact value of the value to some extent; approximately or reasonably close to the value; almost). If the imprecision provided by "about" is not otherwise understood in this ordinary sense in the art, "about" as used in the present invention at least indicates the variation that can be produced by the ordinary methods of measuring and using such parameters. For example, "about" may include a variation of less than or equal to 5%, optionally less than or equal to 4%, optionally less than or equal to 3%, optionally less than or equal to 2%, optionally less than or equal to 1%, optionally less than or equal to 0.5%, and in some aspects, optionally less than or equal to 0.1%.

[0026] Additionally, disclosure of ranges includes disclosure of all values ​​within the entire range and further divided ranges, including endpoints and sub-ranges given for such ranges.

[0027] When silicon-based negative electrodes are applied to all-solid-state batteries, the following problems arise: existing conductive agents are usually carbon materials, which can cause the solid electrolyte to decompose and produce byproducts with poor ion conductivity at the interface between the negative electrode and the solid electrolyte membrane, thereby causing the cycle performance and rate performance of the all-solid-state battery to deteriorate.

[0028] In order to solve the above problem, the present invention proposes a technical solution.

[0029] The first aspect of the present invention provides a negative electrode for an all-solid-state battery, wherein the negative electrode comprises a negative electrode active material layer, wherein the negative electrode active material layer comprises silicon powder and metal powder, wherein the electronic conductivity of the metal powder is 10 4 S / cm~10 7 S / cm.

[0030] In all-solid-state batteries using silicon-based negative electrodes, carbon materials are generally used as conductive agents. However, carbon materials can cause the solid electrolyte in the solid-state battery to decompose, and produce byproducts with poor ionic conductivity at the interface between the negative electrode and the solid electrolyte membrane, thereby causing the cycle performance and rate performance of the all-solid-state battery to deteriorate. Therefore, metal powder is used in the present invention instead of conventional carbon materials.

[0031] Since the electronic conductivity of metal powder is better than that of pure silicon material, when the battery is charged, lithium ions are preferentially lithiated with metal powder, which helps lithium ions to be better embedded in the negative electrode and improve the ionic conductivity of the entire negative electrode, thereby facilitating the improvement of battery capacity performance and preventing lithium precipitation at the negative electrode due to insufficient kinetics of silicon material. In addition, metal powder forms Li-metal alloy after reacting with lithium ions, which has better flexibility than silicon material and is beneficial for buffering the volume expansion caused by the silicon lithiation process, thereby reducing cracking of the negative electrode and improving the cycle performance of the battery.

[0032] In specific applications, the electronic conductivity of the metal powder can be selected to be 10 above the end value of the range. 4 S / cm, 10 7 S / cm, you can also select any value in the above range. For example, 10 5 S / cm, 10 6 S / cm, etc. The above values ​​are only examples and are not limiting.

[0033] In some embodiments, the metal powder includes at least one of indium powder, tin powder, magnesium powder, copper powder, aluminum powder, and iron powder.

[0034] The term "at least one" as used in the present invention refers to any one of the materials listed above, or more than one material can be selected and mixed. The present invention can be freely implemented within the scope of understanding of those skilled in the art. The present invention does not impose any limitation on this.

[0035] In some preferred embodiments, the metal powder includes at least indium powder.

[0036] In some embodiments, based on 100% of the mass of the negative electrode active material layer, the mass of the metal powder accounts for 10% to 30%.

[0037] If the mass proportion of metal powder in the active material layer is too high, it will be detrimental to the energy density of the battery, and further affect the capacity of the battery. Therefore, in the present invention, the mass proportion of metal powder in the negative electrode active material layer is limited to the above range, which can not only meet the battery's conductive performance but also have both the battery's energy density and capacity.

[0038] In specific applications, the mass percentage of the metal powder can be selected from the above range endpoints of 10% and 30%, and can also be any value in the above range, such as 15%, 20%, 25%, etc. The above values ​​are only examples and are not limiting.

[0039] In some embodiments, the particle size of the silicon powder is 1 μm to 6 μm, and the particle size of the metal powder is 0.05 μm to 3 μm.

[0040] In specific applications, the particle size of silicon powder can be selected from any value in the above range, except for the endpoint values ​​of 1μm and 6μm. For example, 2μm, 3μm, 4μm, 5μm, etc. The particle size of metal powder can be selected from any value in the above range, except for the endpoint values ​​of 0.05μm and 3μm. For example, 1μm, 1.5μm, 2μm, 2.5μm, etc. The above values ​​are only examples and are not limiting.

[0041] In some preferred embodiments, the particle size ratio of silicon powder to metal powder is 10:1 to 100:1.

[0042] If the particle size ratio of silicon powder to metal powder is too small, gaps will accumulate between the powder particles, and the ionic conductivity and electronic conductivity in the gaps are poor, which will easily cause lithium deposition and lead to battery failure. Therefore, the present invention limits the particle size ratio of silicon powder to metal powder within the above range, which can effectively avoid lithium deposition.

[0043] In specific applications, the particle size ratio of silicon powder to metal powder can be selected from any value in the above range, in addition to the end points of the above range 10:1 and 100:1, for example, 20:1, 30:1, 40:1, 50:1, 60:1, 70:1, 80:1, 90:1, etc. The above values ​​are only examples and are not limiting.

[0044] In some embodiments, the negative electrode does not include a carbon-based conductive material.

[0045] The present invention does not contain commonly used carbon-based conductive materials as conductive agents, which can prevent the carbon-based conductive materials from causing the solid electrolyte in the solid-state battery to decompose and produce by-products with poor ion conductivity at the interface between the negative electrode and the solid electrolyte membrane, thereby causing the cycle performance and rate performance of the all-solid-state battery to deteriorate.

[0046] In some embodiments, the porosity of the negative electrode active material layer is 5% to 12%.

[0047] The porosity of the negative electrode active material layer referred to in the present invention refers to the pores formed by the accumulation of silicon powder and metal powder.

[0048] In some embodiments, the negative electrode active material layer further includes a binder.

[0049] In a specific application, the binder includes at least one of polyvinylidene fluoride, poly(vinylidene fluoride-hexafluoropropylene), polyvinyl alcohol, polyacrylic acid, polyethylene glycol, polyethylene oxide, poly(p-phenylene oxide), poly(methyl methacrylate), polyacrylonitrile, or polyvinyl chloride (PVC).

[0050] In some embodiments, based on 100% of the mass of the negative electrode active material layer, the mass proportion of the binder is 0.1% to 2%.

[0051] In specific applications, the mass percentage of the binder can be selected from any value in the above range, in addition to the end points of the above range of 0.1% and 2%, for example, 0.5%, 1%, 1.5%, etc. The above values ​​are only examples and are not limiting.

[0052] A second aspect of the present invention provides a method for preparing a negative electrode, the method comprising the following steps:

[0053] S1, mixing silicon powder, metal powder and a binder in a solvent to form a negative electrode slurry;

[0054] S2, coating the negative electrode slurry onto the negative electrode current collector and drying to form a negative electrode.

[0055] In some preferred embodiments, step S1 may further include:

[0056] S11, dry-mixing silicon powder and metal powder to form a mixture;

[0057] S12, uniformly mixing the mixture with the binder and the solvent to form a negative electrode slurry.

[0058] The third aspect of the present invention proposes an all-solid-state battery, an all-solid-state battery, comprising a positive electrode, a solid electrolyte membrane and a negative electrode, wherein the negative electrode is such as the negative electrode described in the first aspect or the negative electrode prepared by the method described in the second aspect, and the negative electrode does not contain a solid electrolyte.

[0059] In some embodiments, the positive electrode includes a positive electrode current collector and a positive electrode active material layer, and the positive electrode active material layer includes a positive electrode active material, a conductive agent, and a binder.

[0060] In specific applications, the positive electrode active material can be selected to include any one or a combination of at least two of lithium cobalt oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, lithium manganese oxide, lithium iron manganese phosphate, lithium vanadium phosphate, lithium vanadium oxyphosphate, lithium iron phosphate, lithium titanate or lithium-rich manganese elastic-based materials. The above are all common positive electrode active materials in the art, which are only examples and not limitations.

[0061] In specific applications, the conductive agent may include any conductive material as long as it does not cause chemical changes. Conductive materials include carbon-based materials (e.g., natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fiber, etc.), metal-based materials (e.g., metal powder, metal fiber, etc., including, for example, copper, nickel, aluminum, silver, etc.), conductive polymers (e.g., polyphenylene derivatives) and mixtures thereof. The above are all common conductive agents in the art, which are only examples and not limitations.

[0062] In specific applications, the binder may include at least one of polyvinylidene fluoride, poly(vinylidene fluoride-hexafluoropropylene), polyvinyl alcohol, polyacrylic acid, polyethylene glycol, polyethylene oxide, poly(p-phenylene oxide), poly(methyl methacrylate), polyacrylonitrile, or polyvinyl chloride (PVC). The above are all common binders in the art, which are only examples and not limitations.

[0063] In some embodiments, the solid electrolyte membrane includes any one or a combination of at least two of a sulfide solid electrolyte, a halide solid electrolyte, and an oxide solid electrolyte. The above are all common solid electrolytes in the art and are only examples and not limitations.

[0064] In some preferred embodiments, the solid electrolyte membrane material may be a sulfide solid electrolyte.

[0065] In specific applications, the sulfide solid electrolyte can be selected from: Li2S-P2S5, Li2S-P2S5-MS x (where M is Si, Ge and Sn and 0≤x≤2), Li 3.4 Si 0.4 P 0.6 S4, Li 10 GeP2S 11.7 O 0.3 , Li 9.6 P3S 12 、Li7P3S 11 、Li9P3S9O3、Li 10.35 Si 1.35P 1.65 S 12 、 Li 9.81 Sn 0.81 P 2.19 S 12 、 Li 10 (Si 0.5 Ge 0.5 )P2S 12 、 Li(Ge 0.5 Sn 0.5 )P2S 12 、 Li(Si 0.5 Sn 0.5 )PsS 12 、 Li 10 GeP2S 12 (LGPS), Li6PS5X (where X is Cl, Br or I), Li7P2S8I, Li 10.35 Ge 1.35 P 1.65 S 12 、 Li 3.25 Ge 0.25 P 0.75 S4, Li 10 SnP2S 12 、 Li 10 SiP2S 12 、 Li 9.54 Si 1.74 P 1.44 S 11.7 C l0.3 、 (1-x) P2S 5-x Li2S (where 0.5 ≤ x ≤ 0.7) or at least one of them.

[0066] In a specific application, the halide solid electrolyte can be selected from: Li2CdC l4 、 Li2MgC l4 、 Li2Cd I4 、 Li2ZnI4, Li3OCl, LiI, Li5ZnI4, Li3OCl 1-x Br x (where 0 < x < 1) or at least one of them.

[0067] In a specific application, the oxide solid electrolyte can be selected from: perovskite type, garnet type, LISICON type, NASICON type, where the perovskite type solid electrolyte material is preferably LLTO (lithium lanthanum titanate / lithium titanate lanthanum, Li 0.33 La 0.56 TiO3), and the garnet type solid electrolyte material is preferably LLZO (lithium lanthanum zirconate / zirconate lanthanum lithium, Li7La3Zr2O 12), NASICON (sodium super ion conductor) type solid electrolyte material is preferably lithium aluminum titanium phosphate LATPLi 1.3 Al 0.3 Ti 1.7 (PO4)3) at least one.

[0068] The embodiments of the present invention will be described in detail below through examples and comparative examples. All examples and comparative examples are all solid-state battery sample groups prepared by the same process, and the number of samples in each group is 20.

[0069] It should be noted that the embodiments of the present invention are not limited to these examples.

[0070] Example 1

[0071] 1. Preparation of positive electrode:

[0072] NCM811, PTFE, super-P and Li2ZrCl6 were mixed evenly in a mass ratio of 70:3:2:25, put into a high shear force equipment mixer, and subjected to fiberization treatment to form a first mixed material, which was then rolled to form a positive electrode active material layer; the rolling temperature was 60°C, and the rolling time was 5 minutes; the positive electrode current collector and the positive electrode active material layer were stacked, hot pressed, and cooled to form a composite positive electrode. The hot pressing temperature was 150°C, the hot pressing time was 10 minutes, and the hot pressing pressure was 120Mpa.

[0073] 2. Preparation of negative electrode:

[0074] Silicon powder and indium powder are dry-mixed to form a second mixture, the mixture is evenly mixed with a binder PVDF and a solvent NMR to form a negative electrode slurry, the negative electrode slurry is coated on a copper foil, and dried to form a negative electrode.

[0075] The mass ratio of silicon powder, indium powder and binder is 79:20:1;

[0076] The particle size of silicon powder is 3μm, and the particle size of indium powder is 0.1μm. The particle size ratio of the two is 30:1;

[0077] The electronic conductivity of silicon is 3×10 -5 S / cm, the electronic conductivity of indium is 4×10 6 S / cm.

[0078] 3. Preparation of solid electrolyte membrane

[0079] The sulfide electrolyte Li6PS5Cl and polytetrafluoroethylene (PTFE) were mixed in a mass ratio of 96:4 to obtain a mixture, which was ground for 30 minutes to obtain a sulfide electrolyte sheet. The obtained sulfide electrolyte sheet was hot rolled at a rolling temperature of 120° C. and a rolling time of 10 minutes.

[0080] 4. Preparation of all-solid-state batteries

[0081] The positive electrode prepared in step one, the negative electrode prepared in step two and the solid electrolyte membrane prepared in step three are assembled to form a battery.

[0082] Example 2

[0083] 1. Preparation of positive electrode:

[0084] NCM811, PTFE, super-P and Li2ZrCl6 were mixed evenly in a mass ratio of 70:3:2:25, put into a high shear force equipment mixer, and subjected to fiberization treatment to form a first mixed material, which was then rolled to form a positive electrode active material layer; the rolling temperature was 60°C, and the rolling time was 5 minutes; the positive electrode current collector and the positive electrode active material layer were stacked, hot pressed, and cooled to form a composite positive electrode. The hot pressing temperature was 150°C, the hot pressing time was 10 minutes, and the hot pressing pressure was 120Mpa.

[0085] 2. Preparation of negative electrode:

[0086] Silicon powder and indium powder are dry-mixed to form a second mixture, the mixture is evenly mixed with a binder PVDF and a solvent NMR to form a negative electrode slurry, the negative electrode slurry is coated on a copper foil, and dried to form a negative electrode.

[0087] The mass ratio of silicon powder, indium powder and binder is 89:10:1;

[0088] The particle size of silicon powder is 3μm, and the particle size of indium powder is 0.1μm. The particle size ratio of the two is 30:1;

[0089] The electronic conductivity of silicon is 3×10 -5 S / cm, the electronic conductivity of indium is 4×10 6 S / cm.

[0090] 3. Preparation of solid electrolyte membrane

[0091] The sulfide electrolyte Li6PS5Cl and polytetrafluoroethylene (PTFE) were mixed in a mass ratio of 96:4 to obtain a mixture, which was ground for 30 minutes to obtain a sulfide electrolyte sheet. The obtained sulfide electrolyte sheet was hot rolled at a rolling temperature of 120° C. and a rolling time of 10 minutes.

[0092] 4. Preparation of all-solid-state batteries

[0093] The positive electrode prepared in step one, the negative electrode prepared in step two and the solid electrolyte membrane prepared in step three are assembled to form a battery.

[0094] Example 3

[0095] 1. Preparation of positive electrode:

[0096] NCM811, PTFE, super-P and Li2ZrCl6 were mixed evenly in a mass ratio of 70:3:2:25, put into a high shear force equipment mixer, and subjected to fiberization treatment to form a first mixed material, which was then rolled to form a positive electrode active material layer; the rolling temperature was 60°C, and the rolling time was 5 minutes; the positive electrode current collector and the positive electrode active material layer were stacked, hot pressed, and cooled to form a composite positive electrode. The hot pressing temperature was 150°C, the hot pressing time was 10 minutes, and the hot pressing pressure was 120Mpa.

[0097] 2. Preparation of negative electrode:

[0098] Silicon powder and indium powder are dry-mixed to form a second mixture, the mixture is evenly mixed with a binder PVDF and a solvent NMR to form a negative electrode slurry, the negative electrode slurry is coated on a copper foil, and dried to form a negative electrode.

[0099] The mass ratio of silicon powder, indium powder and binder is 69:30:1;

[0100] The particle size of silicon powder is 3μm, and the particle size of indium powder is 0.1μm. The particle size ratio of the two is 30:1;

[0101] The electronic conductivity of silicon is 3×10 -5 S / cm, the electronic conductivity of indium is 4×10 6 S / cm.

[0102] 3. Preparation of solid electrolyte membrane

[0103] The sulfide electrolyte Li6PS5Cl and polytetrafluoroethylene (PTFE) were mixed in a mass ratio of 96:4 to obtain a mixture, which was ground for 30 minutes to obtain a sulfide electrolyte sheet. The obtained sulfide electrolyte sheet was hot rolled at a rolling temperature of 120° C. and a rolling time of 10 minutes.

[0104] 4. Preparation of all-solid-state batteries

[0105] The positive electrode prepared in step one, the negative electrode prepared in step two and the solid electrolyte membrane prepared in step three are assembled to form a battery.

[0106] Example 4

[0107] 1. Preparation of positive electrode:

[0108] NCM811, PTFE, super-P and Li2ZrCl6 were mixed evenly in a mass ratio of 70:3:2:25, put into a high shear force equipment mixer, and subjected to fiberization treatment to form a first mixed material, which was then rolled to form a positive electrode active material layer; the rolling temperature was 60°C, and the rolling time was 5 minutes; the positive electrode current collector and the positive electrode active material layer were stacked, hot pressed, and cooled to form a composite positive electrode. The hot pressing temperature was 150°C, the hot pressing time was 10 minutes, and the hot pressing pressure was 120Mpa.

[0109] 2. Preparation of negative electrode:

[0110] Silicon powder, indium powder and tin powder are dry-mixed to form a second mixture, the mixture is evenly mixed with a binder PVDF and a solvent NMR to form a negative electrode slurry, the negative electrode slurry is coated on a copper foil, and dried to form a negative electrode.

[0111] The mass ratio of silicon powder, indium powder, tin powder and binder is 79:15:5:1;

[0112] The particle size of silicon powder is 3μm, the particle size of indium powder is 0.1μm, and the particle size of tin powder is 0.1μm. The particle size ratio of silicon powder and mixed metal powder is 30:1;

[0113] The electronic conductivity of silicon is 3×10 -5 S / cm, the electronic conductivity of indium is 4×10 6 S / cm, the electronic conductivity of tin is 9.6×10 4 S / cm.

[0114] 3. Preparation of solid electrolyte membrane

[0115] The sulfide electrolyte Li6PS5Cl and polytetrafluoroethylene (PTFE) were mixed in a mass ratio of 96:4 to obtain a mixture, which was ground for 30 minutes to obtain a sulfide electrolyte sheet. The obtained sulfide electrolyte sheet was hot rolled at a rolling temperature of 120° C. and a rolling time of 10 minutes.

[0116] 4. Preparation of all-solid-state batteries

[0117] The positive electrode prepared in step one, the negative electrode prepared in step two and the solid electrolyte membrane prepared in step three are assembled to form a battery.

[0118] Example 5

[0119] 1. Preparation of positive electrode:

[0120] NCM811, PTFE, super-P and Li2ZrCl6 were mixed evenly in a mass ratio of 70:3:2:25, put into a high shear force equipment mixer, and subjected to fiberization treatment to form a first mixed material, which was then rolled to form a positive electrode active material layer; the rolling temperature was 60°C, and the rolling time was 5 minutes; the positive electrode current collector and the positive electrode active material layer were stacked, hot pressed, and cooled to form a composite positive electrode. The hot pressing temperature was 150°C, the hot pressing time was 10 minutes, and the hot pressing pressure was 120Mpa.

[0121] 2. Preparation of negative electrode:

[0122] Silicon powder and aluminum powder are dry-mixed to form a second mixture, the mixture is evenly mixed with a binder PVDF and a solvent NMR to form a negative electrode slurry, the negative electrode slurry is coated on a copper foil, and dried to form a negative electrode.

[0123] The mass ratio of silicon powder, aluminum powder and binder is 79:20:1;

[0124] The particle size of silicon powder is 3μm, and the particle size of aluminum powder is 0.1μm. The particle size ratio of the two is 30:1;

[0125] The electronic conductivity of silicon is 3×10 -5 S / cm, the electronic conductivity of aluminum is 3.8×10 5 S / cm.

[0126] 3. Preparation of solid electrolyte membrane

[0127] The sulfide electrolyte Li6PS5Cl and polytetrafluoroethylene (PTFE) were mixed in a mass ratio of 96:4 to obtain a mixture, which was ground for 30 minutes to obtain a sulfide electrolyte sheet. The obtained sulfide electrolyte sheet was hot rolled at a rolling temperature of 120° C. and a rolling time of 10 minutes.

[0128] 4. Preparation of all-solid-state batteries

[0129] The positive electrode prepared in step one, the negative electrode prepared in step two and the solid electrolyte membrane prepared in step three are assembled to form a battery.

[0130] Example 6

[0131] 1. Preparation of positive electrode:

[0132] NCM811, PTFE, super-P and Li2ZrCl6 were mixed evenly in a mass ratio of 70:3:2:25, put into a high shear force equipment mixer, and subjected to fiberization treatment to form a first mixed material, which was then rolled to form a positive electrode active material layer; the rolling temperature was 60°C, and the rolling time was 5 minutes; the positive electrode current collector and the positive electrode active material layer were stacked, hot pressed, and cooled to form a composite positive electrode. The hot pressing temperature was 150°C, the hot pressing time was 10 minutes, and the hot pressing pressure was 120Mpa.

[0133] 2. Preparation of negative electrode:

[0134] Silicon powder and indium powder are dry-mixed to form a second mixture, the mixture is evenly mixed with a binder PVDF and a solvent NMR to form a negative electrode slurry, the negative electrode slurry is coated on a copper foil, and dried to form a negative electrode.

[0135] The mass ratio of silicon powder, indium powder and binder is 94:5:1;

[0136] The particle size of silicon powder is 3μm, and the particle size of indium powder is 0.1μm. The particle size ratio of the two is 30:1;

[0137] The electronic conductivity of silicon is 3×10 -5 S / cm, the electronic conductivity of indium is 4×10 6 S / cm.

[0138] 3. Preparation of solid electrolyte membrane

[0139] The sulfide electrolyte Li6PS5Cl and polytetrafluoroethylene (PTFE) were mixed in a mass ratio of 96:4 to obtain a mixture, which was ground for 30 minutes to obtain a sulfide electrolyte sheet. The obtained sulfide electrolyte sheet was hot rolled at a rolling temperature of 120° C. and a rolling time of 10 minutes.

[0140] 4. Preparation of all-solid-state batteries

[0141] The positive electrode prepared in step one, the negative electrode prepared in step two and the solid electrolyte membrane prepared in step three are assembled to form a battery.

[0142] Example 7

[0143] 1. Preparation of positive electrode:

[0144] NCM811, PTFE, super-P and Li2ZrCl6 were mixed evenly in a mass ratio of 70:3:2:25, put into a high shear force equipment mixer, and subjected to fiberization treatment to form a first mixed material, which was then rolled to form a positive electrode active material layer; the rolling temperature was 60°C, and the rolling time was 5 minutes; the positive electrode current collector and the positive electrode active material layer were stacked, hot pressed, and cooled to form a composite positive electrode. The hot pressing temperature was 150°C, the hot pressing time was 10 minutes, and the hot pressing pressure was 120Mpa.

[0145] 2. Preparation of negative electrode:

[0146] Silicon powder and indium powder are dry-mixed to form a second mixture, the mixture is evenly mixed with a binder PVDF and a solvent NMR to form a negative electrode slurry, the negative electrode slurry is coated on a copper foil, and dried to form a negative electrode.

[0147] The mass ratio of silicon powder, indium powder and binder is 59:40:1;

[0148] The particle size of silicon powder is 3μm, and the particle size of indium powder is 0.1μm. The particle size ratio of the two is 30:1;

[0149] The electronic conductivity of silicon is 3×10 -5 S / cm, the electronic conductivity of indium is 4×10 6 S / cm.

[0150] 3. Preparation of solid electrolyte membrane

[0151] The sulfide electrolyte Li6PS5Cl and polytetrafluoroethylene (PTFE) were mixed in a mass ratio of 96:4 to obtain a mixture, which was ground for 30 minutes to obtain a sulfide electrolyte sheet. The obtained sulfide electrolyte sheet was hot rolled at a rolling temperature of 120° C. and a rolling time of 10 minutes.

[0152] 4. Preparation of all-solid-state batteries

[0153] The positive electrode prepared in step one, the negative electrode prepared in step two and the solid electrolyte membrane prepared in step three are assembled to form a battery.

[0154] Example 8

[0155] 1. Preparation of positive electrode:

[0156] NCM811, PTFE, super-P and Li2ZrCl6 were mixed evenly in a mass ratio of 70:3:2:25, put into a high shear force equipment mixer, and subjected to fiberization treatment to form a first mixed material, which was then rolled to form a positive electrode active material layer; the rolling temperature was 60°C, and the rolling time was 5 minutes; the positive electrode current collector and the positive electrode active material layer were stacked, hot pressed, and cooled to form a composite positive electrode. The hot pressing temperature was 150°C, the hot pressing time was 10 minutes, and the hot pressing pressure was 120Mpa.

[0157] 2. Preparation of negative electrode:

[0158] Silicon powder and indium powder are dry-mixed to form a second mixture, the mixture is evenly mixed with a binder PVDF and a solvent NMR to form a negative electrode slurry, the negative electrode slurry is coated on a copper foil, and dried to form a negative electrode.

[0159] The mass ratio of silicon powder, indium powder and binder is 79:20:1;

[0160] The particle size of silicon powder is 1μm, and the particle size of indium powder is 0.1μm. The particle size ratio of the two is 10:1;

[0161] The electronic conductivity of silicon is 3×10 -5 S / cm, the electronic conductivity of indium is 4×10 6 S / cm.

[0162] 3. Preparation of solid electrolyte membrane

[0163] The sulfide electrolyte Li6PS5Cl and polytetrafluoroethylene (PTFE) were mixed in a mass ratio of 96:4 to obtain a mixture, which was ground for 30 minutes to obtain a sulfide electrolyte sheet. The obtained sulfide electrolyte sheet was hot rolled at a rolling temperature of 120° C. and a rolling time of 10 minutes.

[0164] 4. Preparation of all-solid-state batteries

[0165] The positive electrode prepared in step one, the negative electrode prepared in step two and the solid electrolyte membrane prepared in step three are assembled to form a battery.

[0166] Example 9

[0167] 1. Preparation of positive electrode:

[0168] NCM811, PTFE, super-P and Li2ZrCl6 were mixed evenly in a mass ratio of 70:3:2:25, put into a high shear force equipment mixer, and subjected to fiberization treatment to form a first mixed material, which was then rolled to form a positive electrode active material layer; the rolling temperature was 60°C, and the rolling time was 5 minutes; the positive electrode current collector and the positive electrode active material layer were stacked, hot pressed, and cooled to form a composite positive electrode. The hot pressing temperature was 150°C, the hot pressing time was 10 minutes, and the hot pressing pressure was 120Mpa.

[0169] 2. Preparation of negative electrode:

[0170] Silicon powder and indium powder are dry-mixed to form a second mixture, the mixture is evenly mixed with a binder PVDF and a solvent NMR to form a negative electrode slurry, the negative electrode slurry is coated on a copper foil, and dried to form a negative electrode.

[0171] The mass ratio of silicon powder, indium powder and binder is 79:20:1;

[0172] The particle size of silicon powder is 6μm, and the particle size of indium powder is 0.06μm. The particle size ratio of the two is 100:1;

[0173] The electronic conductivity of silicon is 3×10 -5 S / cm, the electronic conductivity of indium is 4×10 6 S / cm.

[0174] 3. Preparation of solid electrolyte membrane

[0175] The sulfide electrolyte Li6PS5Cl and polytetrafluoroethylene (PTFE) were mixed in a mass ratio of 96:4 to obtain a mixture, which was ground for 30 minutes to obtain a sulfide electrolyte sheet. The obtained sulfide electrolyte sheet was hot rolled at a rolling temperature of 120° C. and a rolling time of 10 minutes.

[0176] 4. Preparation of all-solid-state batteries

[0177] The positive electrode prepared in step one, the negative electrode prepared in step two and the solid electrolyte membrane prepared in step three are assembled to form a battery.

[0178] Example 10

[0179] 1. Preparation of positive electrode:

[0180] NCM811, PTFE, super-P and Li2ZrCl6 were mixed evenly in a mass ratio of 70:3:2:25, put into a high shear force equipment mixer, and subjected to fiberization treatment to form a first mixed material, which was then rolled to form a positive electrode active material layer; the rolling temperature was 60°C, and the rolling time was 5 minutes; the positive electrode current collector and the positive electrode active material layer were stacked, hot pressed, and cooled to form a composite positive electrode. The hot pressing temperature was 150°C, the hot pressing time was 10 minutes, and the hot pressing pressure was 120Mpa.

[0181] 2. Preparation of negative electrode:

[0182] Silicon powder and indium powder are dry-mixed to form a second mixture, the mixture is evenly mixed with a binder PVDF and a solvent NMR to form a negative electrode slurry, the negative electrode slurry is coated on a copper foil, and dried to form a negative electrode.

[0183] The mass ratio of silicon powder, indium powder and binder is 79:20:1;

[0184] The particle size of silicon powder is 3μm, and the particle size of indium powder is 1.5μm. The particle size ratio of the two is 2:1;

[0185] The electronic conductivity of silicon is 3×10 -5 S / cm, the electronic conductivity of indium is 4×10 6 S / cm.

[0186] 3. Preparation of solid electrolyte membrane

[0187] The sulfide electrolyte Li6PS5Cl and polytetrafluoroethylene (PTFE) were mixed in a mass ratio of 96:4 to obtain a mixture, which was ground for 30 minutes to obtain a sulfide electrolyte sheet. The obtained sulfide electrolyte sheet was hot rolled at a rolling temperature of 120° C. and a rolling time of 10 minutes.

[0188] 4. Preparation of all-solid-state batteries

[0189] The positive electrode prepared in step one, the negative electrode prepared in step two and the solid electrolyte membrane prepared in step three are assembled to form a battery.

[0190] Comparative Example 1

[0191] 1. Preparation of positive electrode:

[0192] NCM811, PTFE, super-P and Li2ZrCl6 were mixed evenly in a mass ratio of 70:3:2:25, put into a high shear force equipment mixer, and subjected to fiberization treatment to form a first mixed material, which was then rolled to form a positive electrode active material layer; the rolling temperature was 60°C, and the rolling time was 5 minutes; the positive electrode current collector and the positive electrode active material layer were stacked, hot pressed, and cooled to form a composite positive electrode. The hot pressing temperature was 150°C, the hot pressing time was 10 minutes, and the hot pressing pressure was 120Mpa.

[0193] 2. Preparation of negative electrode:

[0194] Silicon powder, superconducting carbon (Super-p), binder PVDF, and solvent NMR are uniformly mixed to form a negative electrode slurry, and the negative electrode slurry is coated on a copper foil and dried to form a negative electrode.

[0195] The mass ratio of silicon powder, superconducting carbon (Super-p), and binder is 89:10:1;

[0196] The particle size of silicon powder is 3 μm; the electronic conductivity of silicon is 3×10 -5 S / cm.

[0197] 3. Preparation of solid electrolyte membrane

[0198] The sulfide electrolyte Li6PS5Cl and polytetrafluoroethylene (PTFE) were mixed in a mass ratio of 96:4 to obtain a mixture, which was ground for 30 minutes to obtain a sulfide electrolyte sheet. The obtained sulfide electrolyte sheet was hot rolled at a rolling temperature of 120° C. and a rolling time of 10 minutes.

[0199] 4. Preparation of all-solid-state batteries

[0200] The positive electrode prepared in step one, the negative electrode prepared in step two and the solid electrolyte membrane prepared in step three are assembled to form a battery.

[0201] Comparative Example 2

[0202] 1. Preparation of positive electrode:

[0203] NCM811, PTFE, super-P and Li2ZrCl6 were mixed evenly in a mass ratio of 70:3:2:25, put into a high shear force equipment mixer, and subjected to fiberization treatment to form a first mixed material, which was then rolled to form a positive electrode active material layer; the rolling temperature was 60°C, and the rolling time was 5 minutes; the positive electrode current collector and the positive electrode active material layer were stacked, hot pressed, and cooled to form a composite positive electrode. The hot pressing temperature was 150°C, the hot pressing time was 10 minutes, and the hot pressing pressure was 120Mpa.

[0204] 2. Preparation of negative electrode:

[0205] Silicon powder, superconducting carbon (Super-p), Li6PS5Cl, binder PVDF, and solvent NMR are uniformly mixed to form a negative electrode slurry, and the negative electrode slurry is coated on a copper foil and dried to form a negative electrode.

[0206] The mass ratio of silicon powder, superconducting carbon (Super-p), Li6PS5Cl, and binder is 79:10:10:1;

[0207] The particle size of silicon powder is 3 μm;

[0208] The electronic conductivity of silicon is 3×10 -5 S / cm.

[0209] 3. Preparation of solid electrolyte membrane

[0210] The sulfide electrolyte Li6PS5Cl and polytetrafluoroethylene (PTFE) were mixed in a mass ratio of 96:4 to obtain a mixture, which was ground for 30 minutes to obtain a sulfide electrolyte sheet. The obtained sulfide electrolyte sheet was hot rolled at a rolling temperature of 120° C. and a rolling time of 10 minutes.

[0211] 4. Preparation of all-solid-state batteries

[0212] The positive electrode prepared in step one, the negative electrode prepared in step two and the solid electrolyte membrane prepared in step three are assembled to form a battery.

[0213] Comparative experiment

[0214] A total of 12 groups of samples from the above embodiments 1-10 and comparative examples 1-2 were taken and the following tests were performed respectively. All test data were averaged and some values ​​were rounded off.

[0215] 1. First discharge capacity test

[0216] At room temperature, the prepared battery was discharged at a constant current of 0.1C to a cut-off voltage of 3.0V to obtain the first cycle discharge capacity.

[0217] 2. 200-cycle cycle retention rate

[0218] At room temperature, charge with a current of 0.1C to a charging cut-off voltage of 4.2V, switch to constant voltage charging to a cut-off current of 0.05C, let stand for 0.5h, then discharge with a current of 0.1C to a cut-off voltage of 3.0V, let stand for 0.5h, enter the next charge and discharge cycle, and so on, for a total of 200 charge and discharge cycles.

[0219] 3. 3C / 0.1C capacity retention rate

[0220] At a temperature of 45°C, a fully charged battery is discharged at a current of 3C to a cut-off voltage of 3.0V. The capacity obtained by the test is C1, and C1 / C0 is the 3C discharge capacity retention rate below.

[0221] 4. Battery internal resistance test

[0222] Obtained through DCR test, 25℃, 3C discharge for 10 seconds.

[0223] The test results are shown in the following table:

[0224]

[0225]

[0226] It can be seen from the above table Examples 1-10 and Comparative Examples 1-2 that the use of metal powder in the negative electrode instead of carbon-based conductive materials can effectively reduce the decomposition of solid electrolytes caused by carbon materials. Due to the good conductivity of the metal powder, the electronic conductivity of the negative electrode system can be effectively improved, which is beneficial to the improvement of battery capacity performance. The Li-metal alloy formed by the metal powder and lithium is more flexible than the silicon material, which is beneficial to buffer the volume expansion caused by the silicon lithiation process, reduce the cracking of the negative electrode, and is beneficial to improve the cycle performance of the battery. In addition, the absence of a solid electrolyte in the negative electrode is beneficial to the improvement of the battery energy density.

[0227] It should be pointed out that the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A negative electrode for an all-solid-state battery, the negative electrode comprising a negative electrode active material layer, characterized in that: The negative electrode active material layer includes silicon powder and metal powder, wherein the electronic conductivity of the metal powder is 10 4 S / cm~10 7 S / cm.

2. The negative electrode according to claim 1, characterized in that The metal powder includes at least one of indium powder, tin powder, magnesium powder, copper powder, aluminum powder and iron powder.

3. The negative electrode according to claim 1, characterized in that Based on the mass of the negative electrode active material layer being 100%, the mass of the metal powder accounts for 10% to 30%.

4. The negative electrode according to claim 1, characterized in that The particle size of the silicon powder is 1 μm to 6 μm, and the particle size of the metal powder is 0.05 μm to 3 μm.

5. The negative electrode according to claim 1, characterized in that The negative electrode does not include a carbon-based conductive material.

6. The negative electrode according to claim 1, characterized in that The porosity of the negative electrode active material layer is 5% to 12%.

7. The negative electrode according to claim 1, characterized in that The negative electrode active material layer further includes a binder.

8. The negative electrode according to claim 1, characterized in that Based on the mass of the negative electrode active material layer being 100%, the mass of the binder accounts for 0.1% to 2%.

9. A method for preparing a negative electrode, characterized in that: The steps include: S1, mixing silicon powder, metal powder and a binder in a solvent to form a negative electrode slurry; S2, coating the negative electrode slurry onto a negative electrode current collector, and drying to form a negative electrode.

10. An all-solid-state battery, comprising a positive electrode, a solid electrolyte membrane and a negative electrode, wherein: The negative electrode is the negative electrode according to any one of claims 1 to 8 or the negative electrode prepared by the method according to claim 9; The negative electrode does not include a solid electrolyte.

Citation Information

Patent Citations

  • All-solid-state battery with silicon negative electrode and sulfide solid electrolyte

    CN110233282A

  • Negative electrode material layer suitable for all-solid-state battery, preparation method of negative electrode material layer, negative plate and all-solid-state battery

    CN112133920A

  • Negative pole piece, solid-state battery and preparation method of negative pole piece

    CN113991058A

  • Silicon negative electrode suitable for all-solid-state battery, all-solid-state soft package battery and preparation method of silicon negative electrode

    CN117913221A

  • KR20240163785A